Factors that influence Malaysian reit performance / Mohd Amin Che Mohamood - Che Mohamood, Mohd Amin (2011)
This study examines the factors that influence Malaysian Reit performance over a period of August 2005 to December 2010. The researcher build a model that consist of four explanatory variables which are stock market performance, interest rate, inflation rate, and direct real estate market performance. The researcher found that all independent variables are significant at 0.050 significant level. Besides that the researcher also found that among these four independent variables, stock market performance has highest effect on Malaysian Reit performance. However, the multiple coefficient of determination shows that these explanatory variables can explain only 70% of the changes in Malaysian Reit performance, which indicates that there are other factors that significantly influence Malaysian Reit performance that being excluded from the model used by the researcher